Effect of overlay but not electronic blue filters on reading time and eye movements of children with developmental dyslexia - José A. Barela; Rafaela C. Mazzolani; Isabela H. Garrett; Ana Maria F. Barela; Michel A. Hospital; Gabriella A. Figueiredo (Frontiers in Language Sciences)
This study aimed to examine the effects of colored blue electronic and overlay filters on reading time and eye movements of children with and without dyslexia. Children with (n = 15, 11.1 ± 1.6 years old) and without dyslexia (n = 15, 10.6 ± 1.7 years old) seated on a chair, with their heads stabilized by a forehead and chin support. They read different texts shown on a 14-inch laptop screen with no filter, blue electronic filter, and blue overlay filter. Eye movements were recorded using an eye-tracking system (ETG 2.0–SMI), and the total reading time duration, number and duration of fixation, and number and duration of saccades were obtained. Children with dyslexia showed longer reading durations and higher numbers of both fixations and saccades. In addition, they read faster with the blue overlay filter compared with the other conditions. Furthermore, the blue overlay filter reduced the fixation duration and increased the saccade duration. These results show that a blue overlay filter improves reading time in children with dyslexia owing to changes in eye movement patterns.